The Methodology for Selecting a Promising Functional Specialization of а Suburban Rural Settlement - Kuzmenko, Tetiana; Liakh, Vasyl; Dmytrenko, Andrii; Trehubov, Kostiantyn (International Journal of Engineering and Technology, 2018)
A retrospective analysis of the rural settlements’ typology has been carried out; the most common types of suburban rural settlements (SRS) have been identified: satellites, recreational and production ones. Within these basic types, 14 possible SRS subtypes are proposed. Modern tendencies in changes of SRS functional and planning organization are revealed. These changes relate to the deterioration of the cultural and domestic service sector, a significant increase in the rural settlement area with a decrease in its population, stratification of rural population by employment, income, ownership ratio, etc. Functional-planning organization of SRS is conditioned by its specialization. Functional specialization of a settlement, or formation a certain new type based on the traditional settlement, depends on the settlement’s resources. The analysis has defined the determinants of the development and formation of functional SRS type, and has revealed the parameters that determine the total effect of these factors. To determine the functional type of settlement as a strategy for its development, the methodology of the point’s assessment of the determining parameters characterizing the settlement’s resources is proposed. The algorithm of definition of suburban rural settlements’ functional specialization is developed, which provides comparison of alternative variants of SRS functional specialization.
Keywords: suburban zone; functional and planning organization; suburban rural settlement (SRS); algorithm of choice; functional specialization